Dual‐polarized dielectric resonator antenna array. Issue 1 (January 2016) - Rana, Biswarup; Parui, Susanta Kumar
ABSTRACT: A rectangular dielectric resonator antenna (RDRA) fed by two orthogonally direct microstrip lines is designed to obtain dual‐polarization. It excites fundamental TE111 mode for efficient radiation. A four‐element linear array with the said antenna has been designed at a center frequency of 6.55 GHz for obtaining higher directive gain as well as dual‐polarization characteristics. A prototype has been fabricated with Arlon AD270 substrate and experimental measurements have been performed. It offers an impedance bandwidth of 9.4% covering frequency from 6.27 to 6.87 GHz with a maximum gain of 11.8 dBi at the resonant frequency. A good agreement has been obtained between the measured and simulated results. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:24–27, 2016